Immediate implant-based breast reconstruction following mastectomy is not associated with delays in adjuvant therapy - Paz, Lilian; Biazús, Jorge (Frontiers in Oncology, 2026)
BackgroundImmediate breast reconstruction (IBR) following mastectomy is an integral component of breast cancer surgery and contributes to improved quality of life. However, its association with higher postoperative complication rates has raised concerns about potential delays in the initiation of adjuvant therapy, which may negatively impact oncologic outcomes. This study aimed to evaluate whether immediate implant-based breast reconstruction affects the timing of adjuvant treatment.MethodsThis retrospective cohort included 930 women with stage I–III invasive breast cancer who underwent mastectomy between 2018 and 2022. Patients were stratified into two groups based on surgical approach: mastectomy with IBR (n = 200) and mastectomy without IBR (n = 730). The primary outcome was time from definitive cancer surgery to initiation of the first adjuvant treatment (chemotherapy or radiotherapy). A delay was defined as an interval exceeding 12 weeks. Logistic regression models were used to assess factors associated with treatment delay.ResultsThe cohort was composed predominantly of Black women (91%). Women who underwent IBR initiated adjuvant therapy earlier than those without reconstruction [11.0 (IQR 8.0–14.0) vs. 12.0 (IQR 9.0–16.0) weeks; p < 0.01], with fewer experiencing delays beyond 12 weeks (33.3% vs. 47.4%, p < 0.01). While IBR was associated with lower odds of delay in univariate analysis (OR 0.55; 95% CI, 0.39–0.76), this association was attenuated and not statistically significant after adjustment in the multivariable analysis (OR 0.69; 95% CI, 0.46–1.01). Independent predictors of delay included clinical stage III and surgery during the COVID-19 pandemic (2020–2022). Delays were more pronounced among patients scheduled for radiotherapy.ConclusionIn this real-world cohort with predominant representation of Black women, immediate implant-based breast reconstruction after mastectomy did not delay the initiation of adjuvant therapy. IBR can be safely integrated into breast cancer treatment planning without compromising timely access to care, although factors such as advanced disease stage and healthcare workflow remain key contributors to treatment delays. Registry: Brazilian Clinical Trials Registry (ReBEC), RBR-3h369zf.